EXPATRIATE NGO STAFFS’ ADAPTATION STRATEGIES TO VIETNAMESE CULTURE = Những chiến lược thích nghi với văn hóa Việt Nam của người nước ngoài làm việc cho các tổ chức phi chính phủ - Bùi, Thị Khánh Huyền (2020)
Statistics from Institute for Studies of Society in 2013 have shown that there were more than 4,000 expatriates working in over 1000 active non-governmental organizations which make great contribution to the development of Vietnam. Culture shock appeared to be the common unavoidable phenomenon among these foreigners which affects their working results and their lives in Vietnam. Deeply concerned about the issue, the researcher conducted this study with a hope to havean insight into these expatriate NGO’s staffs’ culture shock and their culturalb adaptation in Vietnam. Six expatriate NGO’s staffs who have lived in Vietnam from more than six months were interviewed to discuss their experience in the new culture. They admitted suffering culture shock in various aspects of life and work, especially in physical environment, traffic, language barrier and local people’ behaviors. Assimilation and Hybridity modes were selected by the six participants as the strategies to overcome these difficulties. Individual influences including participants’ understanding about Vietnam, expectations and cultural experience came out to be the most influential factors in their cultural adaptation process. The findings could be of value as a reference for not only expatriates coming to Vietnam but also human resource officers when proposing appropriate policies to facilitate their foreign employees to cope with culture shock.